The Analysis of the Influence of Muslim-Friendly Tourism Destinations on Inbound in Countries in the Asia Pacific Region - Sutikno Sutikno; Fitri Lesia Herdini; Alifah Rokhmah Idialis; Mohd. Shukri Hanapi (Universitas Muhammadiyah Malang, 2023)
The Muslim population become an important consumer market worldwide and an increasingly competitive segment for the halal tourism business sector. Many Muslim-friendly tourist destinations in Asia-Pacific are currently being offered by OIC and non-OIC countries to make tourism a driving force for their economy. This study uses data sources released by the Global Muslim Travel Index (GMTI) for the period 2015 to 2019. The population scope is the countries of the Asia-Pacific region, namely: China, Hong Kong, Japan, South Korea, Brunei, Cambodia, Indonesia, Laos, Malaysia, Philippines, Singapore, Thailand, Australia, Fiji, New Zealand, Bangladesh, India, Maldives, Pakistan and Sri Lanka. The results found that seven independent variables namely: visa, communication, outreach, safety, airport, restaurant, and hotel have a significant effect on inbound logs in countries in the Asia-Pacific region in 2015 to 2019. However, the results of the t test show that there are only three independent variables that have a significant effect on the arrival rate of foreign tourists, namely the Safety, Restaurant and Hotel variables. The results of this study contribute to enriching discourse for countries wishing to develop halal tourist destinations.